Analysis of Crystal Structure the BaTiO\(_3\) and ZrO\(_2\)-doped (Bi\(_0._5\)Na\(_0._5\))TiO\(_3\) with X-ray Diffraction Techniques Using the Rietveld Method - Engkir Sukirman; Syahfandi Ahda; . Mardiyanto (New Visions in Science and Technology Vol. 3, 2021)
The crystal structures of a compound of (Bi0.5Na0.5)TiO3 (BNT) doped with BaTiO3 (BT) and ZrO2 were analyzed. There were three types of samples prepared: (Bi0.5Na0.5)0.93Ba0.05Zr0.02TiO3 (BNBZT1), (Bi0.5Na0.5)0.90Ba0.05Zr0.05 (BNBZT2) and (Bi0.5Na0.5)0.85Ba0.05Zr0.10TiO3 (BNBZT3). The samples were made utilizing Bi2O3, Na2CO3, BaCO3, TiO2, and ZrO2 powders as basic materials in a solid-state reaction technique. The basic components were combined for 3 hours in an agate mortar. A 3,000 psi hydraulic press was used to turn a precursor into pellets. Pellets were calcined for an hour at 300°C, then sintered for 5 hours at 1000°C. X-ray diffraction techniques employing the Rietveld method and Raman spectroscopy were used to characterize the materials. The results of the research revealed that BNT doped BT and ZrO2 had a tetragonal structure, space group I4/mcm, Volume I, No.140 with lattice parameters a = b = 5.519 (2) Å, c = 7.808 (4) Å (BNBZT1), a = b = 5.512 (1) Å, c = 7.798 (5) Å (BNBZT2) and a = b = 5.513 (1) Å, c = 7.800 (2) Å (BNBZT3). For these three samples, Ba2+ and Zr4+ cations entered into the BNT crystal system by partial substitution of cations (Bi, Na)2+. But there were also some Ti3+ cations in the BNBZT3 replaced by Zr4+. Ionic configuration (compound) of BNBZT1, BNBZT2 and BNBZT3 are respectively (Bi0,45Na0,48)0,93Ba0,05Zr0,01TiO3, (Bi0,41Na0,49)0,90Ba0,05Zr0,03TiO3 and (Bi0,42Na0,43)0,85Ba0,05Zr0,01(Ti0,97Zr0,03)O3.